The Influence of Instructional Leadership on Professional Competence Mediated by Self-Efficacy and Social Capital - Herawati, Reni; Tjahjono, Heru Kurnianto (Jurnal Manajemen Bisnis, 2020)
The term of professional competence is regarded as a crucial variable in human resource theory, especially in education. Empirical data have shown that professional competence affected teacher quality; hence, it influenced learning’s effectiveness. The role of principal leadership is notable in the development of teacher professional competence. Some researchers argued that the school principal leadership model, which links to the development of teacher professional competence, is 'instructional leadership.' Some studies concluded that 'self-efficacy' influenced the development of teacher professional competence. Accordingly, some experts presented 'social capital' as a construct that has a good impact on teacher professional competence.  It is essential to dedicate a novelty to respond to this theoretical gap related to the study of all the constructs stated above. Therefore, this paper is intended to present a proposition model of the influence of instructional leadership on professional competence mediated by self-efficacy and social capital.